On an axiological dimension of rigour in school mathematics - Bourgade, Jean-Pierre (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
Abstract In this paper, we seek to identify some elements of a professional teaching logos regarding rigour and point out an axiological dimension of this logos. In contrast to a more autonomous approach to rigour in the field of mathematical production, many teachers’ justifications to their expectations about rigour are based on ethical or aesthetical grounds. The exploration of a possible link between this axiologisation of rigour and the social reproduction of the profession of mathematics teacher is also considered. Résumé Dans cet article, nous cherchons à identifier quelques éléments d’un logos professionnel des enseignants de mathématiques en relation avec la rigueur ; nous mettons en évidence une dimension axiologique de ce logos dans la mesure où nombre d’explications fournies par les enseignants concernant leurs attentes de rigueur sont fondées sur des considérations éthiques ou esthétiques – à la différence de ce qu’on peut observer dans le champ de production mathématique. Nous effectuons également une première exploration d’un lien possible entre cette axiologisation de la rigueur et la reproduction sociale de la profession de professeur de mathématiques.